Pelanggaran Prinsip Kesantunan dalam Video “GURU” - Gusti Alit Mahendra; I Made Madia (Program Magister Linguistik Universitas Udayana, 2020)
This research was conducted aiming to explain the forms of language impoliteness used by daughter against fathers. Speech that contains elements of politeness in language is the main object in this research.